Oral Fast Dissolving Film: A Review - Deshmukh P. Nishant; Dr. Nishan N. Bobade; Dr. Vikrant P. Wankhade; Dr. Sandeep C. Atram; Dr. Shrikant D. Pande; Khedkar S. Anuradha; Patil A. Mahendra (Asian Journal of Pharmaceutical Research and Development, 2025)
Fast-dissolving films are becoming a popular alternative to fast-dissolving tablets. These films dissolve quickly when they come in contact with a wet surface, like the tongue, and can be taken without needing extra liquid. This makes them convenient and helps patients stick to their treatment, especially children, older adults, and people who have trouble swallowing pills or fear choking. Because the drug in these films is absorbed directly into the bloodstream through the mouth, it avoids problems in the digestive system and bypasses the first-pass effect (which happens when the liver breaks down the drug before it reaches the rest of the body). This type of formulation is gaining popularity in over-the-counter products in the U.S. for things like pain relief and motion sickness.